PENGARUH KEDISIPLINAN BELAJAR TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN PKN DI SMA NEGERI 2 SEBERIDA - Ariesa Arasy; Gimin Gimin; Separen Separen (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This research was motivated by a phenomenon that emerged based on the observation that since the implementation of the limited face-to-face learning policy due to the COVID-19 pandemic, many students experienced a decrease in discipline during the learning process, both in participating in learning in terms of collecting assignments and other things. there are still students whose test scores in Civics subjects are lacking or have not reached the minimum completeness criteria (KKM). However, students whose test scores or study results are lacking are not all also less disciplined. The formulation of the problem in this study is whether there is an influence of learning discipline on student learning outcomes in Civics subjects at SMA Negeri 2 Seberida. The purpose of this study is to determine whether there is an influence of learning discipline on student learning outcomes in Civics subjects at SMA Negeri 2 Seberida. And practical benefits, namely as a reference material in carrying out further research that is relevant to this research. Determination of the sample in the study using purposive sampling technique. Data collection methods are observation, interviews, questionnaires, and documentation. Data processing with quantitative descriptive statistical analysis using simple linear regression formula assisted by SPSS version 24 application. The hypothesis in this study is accepted, where there is an influence of learning discipline on student learning outcomes in Civics subjects at SMA Negeri 2 Seberida. This is based on the calculation of the coefficient of determination (R Square) of 0.414 which implies that the influence of the independent variable (learning discipline) on the dependent variable (learning outcomes) is 41.4%.Key Words: Influence, Discipline, Learning Outcomes